Study of Economic Vulnerability and Its Influence on the Economy in Sumatera Island Using the Household Consumption Expenditure Approach - Adin Nugroho; Prientananda Ghina Salsabila (Proceedings of The International Conference on Data Science and Official Statistics, 2023)
The readiness of a region to face shocks and spillover effects from the surrounding area needed to be developed early. Each region had different economic structure so that the policy and strategy that was used to deal with current and future global uncertainties should be different as well. This study aimed to analyze economic vulnerability and the characteristics of its grouping, and analyze the effect of inflation, unemployment rate, foreign investment, and economic vulnerability towards the economy of provinces in Sumatera. The method performed in this study was Cluster Analysis for grouping and creating economic vulnerability variable, Panel Regression Analysis to analyze the effect between variables in general, and GWPR (Geographically Weighted Panel Regression) analysis to analyze spatial effect of regions. The result showed that the variable of economic vulnerability had a negative and significant effect on household consumption expenditures, especially in the Province of Lampung and Sumatera Selatan.